Differentiation of sensory descriptors through co-inoculation of yeast and lactic acid bacteria in wet fermented coffee - Sandy Rodrigues Dias; Nádia Nara Batista; Ana Paula Pereira Bressani; Disney Ribeiro Dias; Rosane Freitas Schwan (Journal of Agriculture and Food Research)
The objective of this study was to evaluate the quality of coffee inoculated with yeasts non-Saccharomyces (Hanseniaspora uvarum CCMA0236 and Pichia kluyveri CCMA0237) and lactic acid bacteria (Lactiplantibacillus plantarum CCMA1065), both single and in co-inoculation, during wet coffee fermentation using the self-induced anaerobiosis method. The microbial composition was monitored by qPCR. The bioactive compounds, carbohydrates, and organic acids by HPLC, volatile compounds by GC‒MS, and sensory characteristics were measured by the cupping test. Fructose (81.77 %) and sucrose (60.64 %) were consumed in the fermentation using co-inoculation of P. kluyveri and L. plantarum. Lactic acid, mainly in the liquid fraction, had higher concentrations with L. plantarum (6.95 g.kg−1) than other fermentation. Trigonelline (42.82 %) and chlorogenic acids (49.68 %) decreased with roasting. One hundred and two volatile compounds were identified in samples. Benzoic acid methyl salicylate was formed during coffee fermentation, contributing to fruity and caramel perception. P. kluyveri showed the highest concentration of esters after fermentation (9.2 mg.kg−1) and in the roasted beans (6.3 mg.kg−1). Wet-processed coffee using SIAF using co-inoculation of H. uvarum and L. plantarum are recommended as they are resistant to stress factors such as pH and competition for nutrients, producing metabolites such as fruity esters, desirable organic acids, contributing to the sweetness and acidity of the coffee beverage with sensory descriptors such as caramel, sweet, spice, fruity, and chocolate, increasing complexity of coffee.